Preliminary Study: Increased Profile of PAI-1 in Lung Cancer Patients Receiving Chemotherapy - Ria Siska Myrnasari; Triwahju Astuti; Suryanti Dwi Pratiwi (Jurnal Respirologi Indonesia, 2018)
Background: Lung cancer has the highest mortality rate in the world. Lung cancer management requires biomarkers to evaluate the chemotherapy response. Levels of Plasminogen Activator Inhibitor-1 (PAI-1) in malignancy >14 ng/ml shows poor prognosis. Increased levels of PAI-1 are associated with stage, metastasis, and prognosis of lung cancer. The chemotherapy is thought to decrease PAI-1 levels. The aim this study is analyze the profile of PAI-1 levels before and after 3rd and 6th chemotherapy cycle and their changes by type of lung cancer and Response Evaluation Criteria in Solid Tumors (RECIST). Methods: This research was conducted from December 2016 to December 2017 at RSSA Malang. The study design was a cohort of 18 lung cancer patients. PAI-1 levels were measured by ELISA in 18 lung cancer stage III or IV patients before (PAI-1(1)) and after 3rd chemotherapy cycle (PAI-1(2)), and 9 patients after 6th chemotherapy cycle (PAI-1(3)). Average PAI-1 levels are presented in tables and graphs. Result: PAI-1(1) 2,151±0,564 ng/ml, PAI-1(2) 1,951±0,534 ng/ml, and PAI-1(3) 1,647±0,495 ng/ml. PAI-1 levels in non-small cell lung carcinoma (NSCLC) were 1.658±0.562 ng/ml and small cell lung carcinoma (SCLC) were 1.609±0.244 ng/ml. Levels of PAI-1(2) in partial response 1.784 ± 0.363 ng/ml, stable disease 1.980 ± 0.304 ng/ml, and progressive disease 2.020±0.635 ng/ml. Levels of PAI-1(3) in the partial response 1.427 ± 0.324 ng/ml and in progressive disease 2.085±0.532 ng/ml. Conclusions: PAI-1 levels in patients with stage III and IV lung cancer after chemotherapy were lower than before chemotherapy, and showed changes corresponding to the response according to RECIST. PAI-1 levels in NSCLC are higher than SCLC. (J Respir Indo 2018; 38(1): 48-56)